Introduction Doing Ritual While Thinking about It? - Gobin, Emma (2018)
Religious anthropology and ritual studies have increasingly acknowledged that ritual and religion are subject to criticism. There is still a tendency, however, to argue that doubt, skepticism, and forms of critical reflexivity' develop somewhere outside the ritual frame', in connection with external processes. In presenting this special section of Religion and Society, this introduction harks back to past research arising out of structural and performative approaches to rite, introduces the notion of critical reflexivity, and outlines the ways it is used to shed light on overlooked formal aspects of religious rituals. In order to stress the subtle connection between ritual action and (local) reflection on this action as evidenced in situ in the course of performance, linked with internal features of ritual activity, the article evokes two lines of empirical inquiry: institutionalized episodes of ritual assessment and ritual accidents' that do not necessarily imply ritual failure'.
Keywords: Christian K. Højbjerg; Anthropology; critical reflexivity; ritual accidents; ritual assessment; ritual criticism; ritual formality; ritual specialists